The Connections between Poverty and Water Supply, Sanitation, and Hygiene in Panama : A Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
The present report summarizes the evidence and findings from a series of studies and new data collection around water supply, sanitation, and hygiene (WASH) and poverty. This WASH poverty diagnostic was undertaken to increase our understanding of the linkages between monetary poverty and WASH services. The work focuses on answering four questions: who are the poor?, does access to WASH vary by poverty level?, what are the synergies between WASH and other sectors, and how does this affect welfare?, and what are the constraints to service and potential solutions to providing universal access to safely managed water supply and sanitation? Although the work done in the context of this diagnostic covered both urban and rural areas, the main focus has been on the rural, and particularly, the indigenous areas, as these are the ones facing the greatest gaps in services. A more in-depth exploration of urban issues has been left for a future date.